TASK-BASED FLIPPED LEARNING INTEGRATED WITH METACOGNITIVE SKILLS TO IMPROVE PROSPECTIVE ENGLISH TEACHERS’ INTERCULTURAL COMMUNICATIVE COMPETENCE - Haerazi Haerazi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTTask-based flipped learning, integrating cultural topics and activities, is explored for its potential in enhancing intercultural communicative competencies (ICCs) in language education. This quasi-experimental study focuses on integrating metacognitive skills into task-based flipped learning to enhance prospective English teachers' ICCs. The participants are divided into experimental and control groups, with data collected through tests and analyzed using parametric statistical methods. The results indicate that metacognitive skills alone have a positive impact on learners' ICCs, with high levels of metacognitive skills correlating with commendable ICCs. Task-based flipped learning is identified as a promising approach for fostering ICCs in language education.ABSTRAKPembelajaran flipped learning berbasis tugas, yang mengintegrasikan topik dan aktivitas budaya, dieksplorasi untuk potensinya dalam meningkatkan kompetensi komunikatif antar budaya (ICC) dalam pendidikan bahasa. Studi quasi-eksperimental ini berfokus pada integrasi keterampilan metakognitif ke dalam pembelajaran flipped learning berbasis tugas untuk meningkatkan ICC calon guru bahasa Inggris. Peserta didik dibagi menjadi kelompok eksperimen dan kontrol, dengan data dikumpulkan melalui tes dan Seiring dengan perkembangan teknologi, platform ini menawarkan pengalaman bermain yang seru dan menegangkan dengan berbagai fitur unggulan yang siap memanjakan para pemainnya.Seiring dengan perkembangan teknologi indohoki77 menawarkan pengalaman bermain yang seru dan menegangkan dengan berbagai fitur unggulan yang siap memanjakan para pemainnya. dianalisis menggunakan metode statistik parametrik. Hasil penelitian menunjukkan bahwa keterampilan metakognitif saja memiliki dampak positif pada ICC peserta didik, dengan tingkat keterampilan metakognitif yang tinggi berkorelasi dengan ICC yang baik. Pembelajaran flipped learning berbasis tugas diidentifikasi sebagai pendekatan yang menjanjikan untuk mengembangkan ICC dalam pendidikan bahasa.How to Cite: Haerazi. (2023). Task-Based Flipped Learning Integrated with Metacognitive Skills to Improve Prospective English Teachers’ Intercultural Communicative Competence. IJEE (Indonesian Journal of English Education), 10(2), 323-339. doi:10.15408/ijee.v10i2.32696.